2020
DOI: 10.1055/s-0040-1714280
|View full text |Cite
|
Sign up to set email alerts
|

High Signal Intensity on Diffusion-Weighted Images Reflects Acute Phase of Deep Vein Thrombus

Abstract: The effects of antithrombotic therapy on deep vein thrombosis (DVT) can be affected by thrombus age, which cannot be reliably determined by noninvasive imaging modalities. We investigated whether magnetic resonance (MR) diffusion-weighted imaging (DWI) can localize and determine the age of venous thrombus in patients with DVT, animal models, and human blood in vitro. Signal intensity (SI) on DWI and the apparent diffusion coefficient (ADC) of thrombi were assessed in eight patients with DVT using a 1.5-T MR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…(92%) as compared to 85% by Grey scale. This finding of present study coincides with that of Gi T et.al (2020) 14. Similarly, it is supported also by SteveGoodacre et.al.…”
supporting
confidence: 94%
“…(92%) as compared to 85% by Grey scale. This finding of present study coincides with that of Gi T et.al (2020) 14. Similarly, it is supported also by SteveGoodacre et.al.…”
supporting
confidence: 94%
“…thrombus age in patients with deep venous thrombosis 30 . A rabbit model of jugular venous thrombus has also indicated that the number of macrophages in the thrombus increases in the thrombus over time 31 . However, it is important to note that CD 163positive cell density increases during the first few days after thrombosis formation and then decreases slowly 32 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…30 A rabbit model of jugular venous thrombus has also indicated that the number of macrophages in the thrombus increases over time. 31 However, it is important to note that CD 163-positive cell density increases during the first few days after thrombosis formation and then decreases slowly. 32 Therefore, we divided the thrombi according to tertiles of CD163-positive cell density based on the assumption that thrombi in the lowest tertile were younger than those in the middle and highest tertiles.…”
Section: Thrombus Agementioning
confidence: 99%
“…The concept is supported by clinical and basic studies using MRI and an animal model of DVT. The median value of the DVT volume calculated by MRI was 20 mL 66 . The value appears to be much larger than that of atherothrombosis.…”
Section: Vtementioning
confidence: 72%